PENGARUH LIKUIDITAS, WAKTU JATUH TEMPO, DAN KUPON OBLIGASI TERHADAP HARGA OBLIGASI PADA PERUSAHAAN KORPORASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sophan Sophian; Elza Delisna Putri (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aimed to find out the effects of the variables of the Liquidity with the Current Ratio as its proxy, Maturity Date Duration, and Bond Coupon on the Bond Price of companies listed in Indonesia Stock Exchange. The period in the study was 4 years, from 2017 to 2020. The research population comprised 116 bonds of companies listed in Indonesia Stock Exchange in the periode 2017-2020. The sampel was selected by means of the purposive sampling technique and it consisted of 14 bonds of companies. The data analysis technique was panel regression analysis. Based on the results of the data analysis, partially the Current Ratio did not have an effect on the Bond Price, the Maturity Date Duration had a significant positive effect on the Bond Price, and the Bond Coupon had a significant positive effect on the Bond Price